METHOD OF COMPUTER-LINGUISTIC VALIDATION OF WEB-COMMUNITY MEMBERS’ INTERNET-NAMES - Федушко, С.; Сєров, Ю.; Ярка, У. (Proceedings of National Aviation University (archive), 2012)
The basic web-communities owners’ administration problem lies in the validation of Web-communityusers’ internet-names. In order to solve this problem the new computer-linguistic approach to the validation of Web-community users’ internet-names has been developed. The rules of internet-names choice and usagehave been developed with the aim of order and control maintenance within online community.